Pre-notched and corroded low cycle fatigue behaviour of a nickel based alloy for disc rotor applications - Karen Perkins (International Journal of Fatigue, 2017)
Currently there is doubt surrounding the suitability of chemically-induced stress independent pre-conditioning of specimens to simulate turbine corrosion prior to fatigue testing. the thick oxide scales developed using such techniques can lead to net section loss and typically a lack of grain boundary sulphide attack seen in components that experience stress. An alternative approach to a corrosion-fatigue test scenario is suggested by micro-notching fatigue specimens prior to low salt flux corrosion to form grain boundary sulphide particles within channel-like features akin to stress assisted morphologies. On fatigue testing, a trend was identified where a change of mechanism was observed. The grain boundary oxide likely formed in the wake of freshly precipitated sulphide particles fractures around segments of grains leading to a metal loss that contributes to a significant reduction in fatigue properties.